2018
DOI: 10.1038/s41598-018-28622-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ABCB1 genetic polymorphisms on the transport of rivaroxaban in HEK293 recombinant cell lines

Abstract: Direct oral anticoagulants (DOAC) are substrates for the ABCB1 transporter (also called P-glycoprotein), an active efflux pump. ABCB1 polymorphisms have been previously reported to influence the pharmacokinetics of several drugs such as immunosuppressants and tyrosine kinase inhibitors. Recently, in vivo studies have suggested that genetic variants might contribute to the inter-individual variability in DOAC plasma concentrations. Therefore, we evaluated the in vitro effect of the most common coding ABCB1 sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…These combined genetic changes led to the estimated half-life of rivaroxaban increasing by threefold in the reported patient [36]. However, this explanation was contradicted by the work done by Sennesael et al [37] who concluded that the ABCB1 1236 C > T-2677G > T-3435C > T and 1199 G > A SNPs had no significant influence on the intracellular accumulation of rivaroxaban when compared to the wild-type protein [37]. But, their work confirmed the role of ABCB1 in transporting the drug.…”
Section: Abcb1 (P-gp)+abcb2 (Bcrp)mentioning
confidence: 83%
See 4 more Smart Citations
“…These combined genetic changes led to the estimated half-life of rivaroxaban increasing by threefold in the reported patient [36]. However, this explanation was contradicted by the work done by Sennesael et al [37] who concluded that the ABCB1 1236 C > T-2677G > T-3435C > T and 1199 G > A SNPs had no significant influence on the intracellular accumulation of rivaroxaban when compared to the wild-type protein [37]. But, their work confirmed the role of ABCB1 in transporting the drug.…”
Section: Abcb1 (P-gp)+abcb2 (Bcrp)mentioning
confidence: 83%
“…The ABCB1 gene is located on chromosome 7 and is composed of 29 exons in a 251.3-kb genomic region [36]. The three most common SNPs in the coding region are rs1128503 (1236 C>T, Gly412Gly), rs2032582 (2677 G>T, Ala893Ser) and rs1045642 (3435 C > T, Ile1145Ile) [37]. They are in strong linkage disequilibrium and present a minor allelic frequency around 50% in the Caucasian population [37].…”
Section: Abcb1 (P-gp)+abcb2 (Bcrp)mentioning
confidence: 99%
See 3 more Smart Citations